2009
DOI: 10.1002/ar.21024
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Craniofacial Morphology in GDF‐8 (Myostatin)‐Deficient Mice

Abstract: It is well recognized that masticatory muscle function helps determine morphology, although the extent of function on final form is still debated. GDF-8 (myostatin), a transcription factor is a negative regulator of skeletal muscle growth. A recent study has shown that mice homozygous for the myostatin mutation had increased muscle mass and craniofacial dysmorphology in adulthood. However, it is unclear whether such dysmorphology is present at birth. This study examines the onset and relationship between hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…Alternatively, these observations could indicate that the window of susceptibility in the low dose animals has shifted to a later time point. However, as calvarial expansion is almost complete at this age, morphometric differences would not be expected at a later post-natal time point as brain expansion and final vault form is complete by approximately 30 days post-natal [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these observations could indicate that the window of susceptibility in the low dose animals has shifted to a later time point. However, as calvarial expansion is almost complete at this age, morphometric differences would not be expected at a later post-natal time point as brain expansion and final vault form is complete by approximately 30 days post-natal [54]. …”
Section: Discussionmentioning
confidence: 99%
“…; Vecchione et al. ), changes in food hardness or consistency (He & Kiliaridis, ; Mavropoulos et al. ), and orthodontic manipulation (Mavropoulos et al.…”
Section: Discussionmentioning
confidence: 99%
“…Diet can be such a late-acting factor that influences growth of the skull by mechanical loading from mastication. Evidence that this process affects human skull shape comes from analyses of populations with different diets (Paschetta et al 2010) and it also has been shown in experimental studies in mice (Renaud et al 2010;Vecchione et al 2010). Overall, genetic and environmental integration are expected to result from a combination of processes that act at different times and produce different patterns that are difficult to tease apart but may have important evolutionary implications (Hallgrímsson et al 2009;Lieberman 2011).…”
Section: Modularity and Integrationmentioning
confidence: 98%